Impact of Different Type and Frequency of Social Participation on Depressive Symptoms Among Older Chinese Adults: Is There a Gender Difference? - Xiao, Shujuan; Lin, Huang; Zhao, Chongbang; Zheng, Xiao; Shi, Lei; Zhang, Jiachi; Xue, Benli; Chang, Jinghui; Chen, Jiangyun; Zhang, Chichen (Frontiers in Psychiatry, 2021)
Objectives: Social participation may prevent depressive symptoms in older adults. But research to date ignores gender differences in the associations between social participation and depressive symptoms. The purpose of this study was to determine the effect of different type and frequency of social participation on depressive symptoms, as well as if there is a gender difference in these correlations among older Chinese adults. Methods: Data was obtained from adults aged 60 years or above in the 2018 China Health and Retirement Longitudinal Survey, a nationally representative sample of older adults in China. Depressive symptoms were measured using CESD-10. Social participation included participation in social groups, hobby groups, sports groups, and community-related organizations. The independent relationships between each type of social participation and depressive symptoms were assessed using multiple linear regression models. Results: A total of 6,287 older adults were included in this analysis, of whom 49.69% were women. Participating in social groups, sports groups, and community-related organizations with a frequency of one or more per week was all linked to better mental health. Furthermore, our findings suggest that the positive relationship between participation in social groups, hobby groups, and community-related organizations and depressive symptoms is more flexible for older men than for women. Conclusions: Older individuals who participate in social participation at a high frequency may have better mental health. The findings provide novel insights into mental health from the standpoint of social participation in older adults. Gender differences in the associations between social participation and depressive symptoms need to be considered when formulating interventions to prevent depression.